The 3’UTRs of Myelin Basic Protein mRNAs Regulate Transport, Local Translation and Sensitivity to Neuronal Activity in Zebrafish - Torvund-Jensen, Julie; Steengaard, Jes; Askebjerg, Liselotte B.; Kjaer-Sorensen, Kasper; Laursen, Lisbeth S. (Frontiers in Molecular Neuroscience, 2018)
Formation of functional myelin sheaths within the central nervous system depends on expression of myelin basic protein (MBP). Following process extension and wrapping around axonal segments, this highly basic protein is required for compaction of the multi-layered membrane sheath produced by oligodendrocytes. MBP is hypothesized to be targeted to the membrane sheath by mRNA transport and local translation, which ensures that its expression is temporally and spatially restricted. The mechanistic details of how this might be regulated are still largely unknown, in particular because a model system that allows this process to be studied in vivo is lacking. We here show that the expression of the zebrafish MBP orthologues, mbpa and mbpb, are developmentally regulated, and that expression of specific mbpa isoforms are restricted to the peripheral nervous system. By analysis of transgenic zebrafish, which express a fluorescent reporter protein specifically in myelinating oligodendrocytes, we demonstrate that both mbpa and mbpb include a 3’UTR sequence, by which mRNA transport and translation is regulated in vivo. Further functional analysis suggests that 1) the 3’UTRs delay the onset of protein expression, and that 2) several regulatory elements contribute to targeting of the mbp mRNA to the myelin sheath. Finally, we show that a pharmacological compound known to enhance neuronal activity stimulates the translation of Mbp in zebrafish in a 3’UTR-dependent manner. A similar effect was obtained following stimulation with a TrkB receptor agonist, and cell-based assays further confirmed that the receptor ligand, BDNF, in combination with other signals reversed the inhibitory effect of the 3’UTR on translation.